PENGARUH NILAI PERUSAHAAN, DEBT TO EQUITY RATIO DAN DIVIDEND PAYOUT RATIO TERHADAP PERATAAN LABA PADA PERUSAHAAN PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Kevin, Kevin; Jesselyn, Gloria Iverose; Jessicca, Jessicca; Erlita, Erlita; Waruwu, Lilis Risna; Sitorus, Friska Darnawaty (Aksara Public, 2019)
This study aims to test and analyze company value, debt to equity ratio and DPR (Dividend Payout Ratio) simultaneously to income smoothing in banking companies listed on the Indonesia Stock Exchange for the 2015-2017 period. The data collection method used is the documentation method. This type of research uses a quantitative approach, based on positivism philosophy and the nature of deductive research. The population in this study were 43 banking companies. The technique used in sampling is purposive sampling, so the sample is 14 companies. Data is analyzed by using multiple linear regression analysis models, determination coefficients, F test, and T test to get a good regression model. The results of the simultaneous and partial hypothesis research show that company value, debt to equity ratio and DPR (Dividend Payout Ratio) have no effect on income smoothing in banking companies listed on the Indonesia Stock Exchange for the 2015-2017 period with significant values> 0.05. The results of the coefficient of determination analysis obtained an adjusted R Square value of -0.034, meaning that the variable value of the company, debt to equity ratio and the House of Representatives (Dividend Payout Ratio) cannot explain the effect on earnings changes. The conclusion from the results of this study is that the value of the company, DER and DPR cannot be used as a predictor of earnings changes.